Exploring English descriptive writing vocabulary acquisition through creative pedagogical strategies - Nur Ehsan Mohd Said; Vanitha Thambirajah; Melor Md Yunus; Tan, Kim Hua; Fazal Mohamed Mohamed Sultan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Review on previous English as a second language (ESL) interventional programmes in Malaysia has indicated limited emphasis on creative pedagogy. Particularly in writing classes that include descriptive writing, a genre that requires writers to be creative and expressive, a significant portion of learners were found to suffer from poor proficiency. Therefore, the present study aimed to explore the impact of creative pedagogical strategies on ESL learners’ descriptive writing. Under classroom research, it adopted the action research design with a single case study to monitor upper secondary school learners’ writing with an emphasis on sentence construction and vocabulary. The data collection involved focus group interviews, written tests, and evaluation of students’ written work. It was revealed that creative pedagogical strategies were effective in improving students’ descriptive writing performance. The main findings derived included five themes as the following: ability to describe pictures using complex vocabulary, learning new words, acquisition of various adjectives and verbs, ability to show emotion or feelings, and acquisition of skill for delivering meaning with precision. We propose a chain of parallel action-related research plans to further investigate creative teaching approaches and to encourage similar creative pedagogical strategies by English teachers in the country.